Efficient detection of Frankliniella schultzei (Thysanoptera, Thripidae) by cytochrome oxidase I gene (mtCOI) direct sequencing and real-time PCR - Leao, Evelynne Urzedo (2017)
Identification of Thysanoptera is based mainly on external morphology examination that can be time-consuming and difficult for non taxonomic experts. In this work, we propose a rapid and efficient molecular method to identify Frankliniella schultzei, an important and widespread pest thrips vector of tospoviruses in South America countries. Species-specific primers designed in the mitochondrial cytochrome oxidase I gene (mtCOI) were optimized for detection by conventional PCR and real-time PCR. The primers were tested on immature and adult thrips collected from crops and weeds found in Sao Paulo State. All samples collected were identified as F. schultzei, indicating the high prevalence of this species as vector of tospoviruses in Brazilian fields.